Pandemic Exposures Economy and Society in the Time of Coronavirus - Fassin, Didier; Fourcade, Marion (HAU Books, 2021)
For people and governments around the world, the onset of the COVID-19 pandemic seemed to place the preservation of human life at odds with the pursuit of economic and social life. Yet this simple alternative belies the complexity of the entanglements the crisis has created and revealed not just between health and wealth but also around morality, knowledge, governance, culture, and everyday subsistence. Didier Fassin and Marion Fourcade have assembled an eminent team of scholars from across the social sciences conducting research on six continents to reflect on the multiple ways the coronavirus has entered, reshaped, or exacerbated existing trends and structures in every part of the globe. The contributors show how the disruptions caused by the pandemic have both hastened the rise of new social divisions and hardened old inequalities and dilemmas. An indispensable volume, Pandemic Exposures provides an illuminating analysis of this watershed moment and its possible aftermath.